2022
DOI: 10.3390/pr10061154
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Dynamic Mathematical Modeling of Heavy Metal Removal with the Biosorption Process

Abstract: Biosorption has great potential in removing toxic effluents from wastewater, especially heavy metal ions such as cobalt, lead, copper, mercury, cadmium, nickel and other ions. Mathematically modeling of biosorption process is essential for the economical and robust design of equipment employing the bioadsorption process. However, biosorption is a complex physicochemical process involving various transport and equilibrium processes, such as absorption, adsorption, ion exchange and surface and interfacial phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 126 publications
1
14
0
Order By: Relevance
“…These findings show that energetically less suitable sites are formed by increasing metal ion concentration in the medium. These results are found to match with other studies. The removal efficiency of Cu 2+ , Cd 2+ , or Cr 3+ ions on Ch-g-Sch I and Ch-g-Sch II at different initial concentrations (300–900 mg L –1 ) is shown in Figure S2. The results indicated that the removal percentage of Cu 2+ , Cd 2+ , and Cr 3+ ions using the Ch-g-PAN Schiff base decreases as the initial concentration of Cu 2+ , Cd 2+ , or Cr 3+ ions increases.…”
Section: Resultssupporting
confidence: 89%
“…These findings show that energetically less suitable sites are formed by increasing metal ion concentration in the medium. These results are found to match with other studies. The removal efficiency of Cu 2+ , Cd 2+ , or Cr 3+ ions on Ch-g-Sch I and Ch-g-Sch II at different initial concentrations (300–900 mg L –1 ) is shown in Figure S2. The results indicated that the removal percentage of Cu 2+ , Cd 2+ , and Cr 3+ ions using the Ch-g-PAN Schiff base decreases as the initial concentration of Cu 2+ , Cd 2+ , or Cr 3+ ions increases.…”
Section: Resultssupporting
confidence: 89%
“…Instead, it was adequately fitted into the FreundlichEXT model, and the relationship exhibited a biphasic isotherm shape. This could suggest that a competitive adsorption had occurred where other components in the adsorbate–adsorbent system could compete with further attachment of DON molecules to the active sites on PYCW [ 61 , 62 ]. This could result in a lower efficacy of PYCW at high DON concentrations as used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Pb(II) adsorption capacity q e (in mg g −1 ) and removal efficiency (%R) were determined using Equations (1) and (2), respectively [ 9 ]. where C 0 and C e (in mg·L −1 ) are the initial and equilibrium final Pb(II) concentrations, respectively, and V (in L) is the volume of solution and m (in g) is the biosorbent mass.…”
Section: Methodsmentioning
confidence: 99%
“…However, these methods have disadvantages such as the high operating costs, long operating times, and the generation of a large volume of toxic sludge [ 5 , 6 ]. In this context, the removal of contaminants using biological materials (biosorbents), such as algae, cyanobacteria, fungi, or particularly agroindustrial wastes has become an economical, ecological, and promising alternative method compared with the conventional methods mentioned above [ 7 , 8 , 9 , 10 ]. These biosorbents can be modified to improve the adsorption capacity, structural stability, and reusability.…”
Section: Introductionmentioning
confidence: 99%